Education Based On Religious Moderation In The Qur'an - Mildawati, Titi; Masrifah, Rofia; Yusuf, Muhammad; Kharisman, Muh.; Mujahid, Ahmad; Indra Adhyaksa, Muhammad (IAIN PAREPARE, 2024)
The increasingly complex diversity of society, encompassing variations in religion, tribe, culture, ethnicity, groups, and organizations, if not based on a deep-rooted understanding of religious moderation, can lead to disputes, egoism, intolerance, discrimination, and extremism, making differences seem problematic. Islam teaches that differences are a blessing from Allah Swt. The objectives of this paper are twofold: first, to provide a comprehensive understanding of the concept of education based on religious moderation; and second, to conduct studies to understand and apply the concept of education based on religious moderation in the study of the Qur'an. This research employs library research methods or literature studies, with data collection carried out in several stages, ranging from collecting references to analyzing them. The study focuses specifically on the concept of religious moderation-based education in the Qur'an. The results reveal several key Qur'anic verses that underpin this concept: QS al-Baqarah / 2:143 emphasizes the prohibition of discriminating between people; QS al-Mulk / 67:3 highlights the importance of maintaining the balance of natural phenomena; QS ash-Sham / 91:7-9 discusses moral values; QS al-Hujurat / 49:13 addresses issues of nation and state; QS Luqman / 31:19 promotes moderation in conduct; QS an-Nisa / 4:58 underscores justice; and QS al-Kafirun / 109:1-6 supports the freedom of religion. The study concludes that the concept of moderation-based education in the Qur'an is well-supported by various verses. These findings imply that integrating cultural education based on local wisdom with religious moderation can help individuals appreciate culture as a form of respect rather than a deviation from religious teachings. The author recommends further research on this integrated approach to enhance the understanding and application of religious moderation in diverse societies.